Ultrasound-guided transvaginal radiofrequency ablation of uterine fibroids assisted by virtual needle tracking system: a preliminary study. (31st December 2018) - Turtulici, Giovanni; Orlandi, Davide; Dedone, Giorgia; Mauri, Giovanni; Fasciani, Alessandro; Sirito, Rodolfo; Silvestri, Enzo
Abstract: Purpose: The purpose of this study was to assess the feasibility and outcome of transvaginal ultrasound (US)-guided radiofrequency ablation of uterine fibroids assisted by a real-time virtual needle tracking (VT) system. Methods: Between January 2017 and February 2018, 19 patients (age 45 ± 8 y, range 36–53 y) with 25 symptomatic uterine fibroids underwent transvaginal radiofrequency ablation (RFA) at a single center. Mean number of fibroids for patient was 1.7 (min, max: 1–3). Patients with more than one fibroid were 10 (52.6%). Uterine fibroids (mean volume: 13.6 mL; range: 5.3–41.9 mL) were treated with a dedicated internally cooled 17 G 35 cm RF needle with 1 cm or variable active tip and the moving shot technique. An electromagnetic system was used for showing a virtual needle during the procedure. Contrast-enhanced ultrasound evaluation was performed before and immediately at the end of procedure. Feasibility of the procedure, technical success rate, volume percentage reduction at 1, 3 and 6 months, clinical outcome (QOL score) and complications were analyzed. Results: Procedure was feasible in 19/19 patients (100%). Technical success was achieved in 100% of 25 treated fibroids. Mean fibroids volume decreased from 13.6 ml at baseline to 5.9 ml at 6 month (reduction rate 62.7%, range 48.5–76.9; p  < .05). No major immediate or late complications occurred. Minor complications occurred in two patients. QOL score significantly improved from 68 ± 36 at baseline to 97 ± 16 at six-months follow-up ( p  < .05). Conclusion: Transvaginal US-guided RFA assisted by a real-time VT system is a feasible, safe and effective technique for the treatment of uterine fibroids.